2019
DOI: 10.3389/fpubh.2019.00355
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lytic Bacteriophages Infecting Multidrug-Resistant Shiga Toxigenic Atypical Escherichia coli O177 Strains Isolated From Cattle Feces

Abstract: The increasing incidence of antibiotic resistance and emergence of virulent bacterial pathogens, coupled with a lack of new effective antibiotics, has reignited interest in the use of lytic bacteriophage therapy. The aim of this study was to characterize lytic Escherichia coli O177-specific bacteriophages isolated from cattle feces to determine their potential application as biocontrol agents. A total of 31 lytic E. coli O177-specific bacteriophages were isolated. A large proportion (71%) of these phage isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…These three tests form the basis for the initial screening of a phage library to identify phages with the broadest host range. The data generated also allowed direct comparison of DST versus EOP, as these two assays are commonly used to characterise phages (Montso et al, 2019; Rivera et al, 2019; Sybesma et al, 2016) [Supplementary Data Table S5 & S6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These three tests form the basis for the initial screening of a phage library to identify phages with the broadest host range. The data generated also allowed direct comparison of DST versus EOP, as these two assays are commonly used to characterise phages (Montso et al, 2019; Rivera et al, 2019; Sybesma et al, 2016) [Supplementary Data Table S5 & S6].…”
Section: Resultsmentioning
confidence: 99%
“…DST is commonly used in the literature to assess the host range of phage (Hyman, 2019; Montso et al, 2019; Sybesma et al, 2016). The data demonstrated that the DST overestimates the host range or clinical isolate coverage of the individual phage by approximately 50% compared with the EOP and the planktonic killing assay (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…STEC control using bacteriophages against STEC contaminated surfaces in cattle farms (e.g., cow hides) and meat products has demonstrated a significant decrease in STEC [ 114 , 139 ]. However, even though in vitro assays have shown promising results [ 137 , 138 , 139 ], in vivo trials have not always been successful. Administration of bacteriophages can result in STEC reduction, although in some studies, the reduction between treatment groups was not significant and in some other studies, there was no reduction at all [ 114 ].…”
Section: Stec Prevention Methods and Future Perspectivesmentioning
confidence: 99%
“…T4-like Myoviridae phages have been found in higher titers in low shedding animals, suggesting that their presence is linked to reduced O157:H7 titers [ 114 ]. Recent studies have further suggested that cattle intestinal endemic phages target specific STEC strains: Myoviridae and Siphoviridae phages target various non-O157 groups [ 137 ]; Myoviridae phages (isolated from cattle feces) target O177, O157, O26 STEC serogroups [ 138 ]; a T4-like phage of the Myoviridae family isolated from the cattle intestine (not from feces) targeted O157:H7 and non-O157 serotypes but not Salmonella strains [ 139 ]. Ciliate protozoa have been reported to predate on STEC, but predation does not appear to be STEC specific [ 47 ].…”
Section: The Native Git Microbiota and Its Interactions With Stecmentioning
confidence: 99%
“…These represent the first set of indigenous bacteriophages to be isolated from tropical Africa. Another study from South Africa [125] reported the characterization of lytic bacteriophages active against multi-drug resistant Escherichia coli 0177 strains isolated from cattle fecal matter. While a study reported the effective use of phage therapy against multi-drug resistant Staphylococcus aureus pneumonia in mice models [126] , no study reporting the successful use of bacteriophage therapy on humans in a clinical setting in Africa was found.…”
Section: Phage Therapy In Africa: Current State Of Knowledgementioning
confidence: 99%